Methicillin-resistant and methicillin-susceptible Staphylococcus aureus in French hedgehogs admitted to a wildlife health center - Marisa Haenni; Séverine Murri; Caroline Lefrère; Jesper Larsen; Antoine Drapeau; Julie Botman; Pauline François; Philippe Gourlay; François Meurens; Jean-Yves Madec (One Health)
The mecC gene conferring methicillin-resistance has always been found on a SCCmec type XI element and is largely restricted to the few clonal complexes CC130, CC1943, CC425, CC49 and CC599. The occurrence of the mecC gene in many different hosts highlighted its One Health importance, even though European hedgehogs (Erinaceus europaeus) are considered its natural reservoir, most probably because of the selective pressure imposed by beta-lactam-producing dermatophytes (Trichophyton erinacei) that colonize the skin of these mammals. Surprisingly, while the presence of T. erinacei on the French territory has been proven, no mecC-positive methicillin-resistant Staphylococcus aureus (MRSA) isolate has been reported yet from hedgehogs. We thus sampled 139 hedgehogs brought to a wildlife center; 128 were S. aureus carriers and 25 (18.0 %) presented a MRSA isolate, of which 21 (15.1 %) displayed the mecC gene. All 161 S. aureus collected were whole-genome sequenced. The mecC-MRSA belonged to the classical CCs, i.e. CC130, CC1943 and CC49. The majority (98/139, 70.5 %) of the methicillin-susceptible Staphylococcus aureus (MSSA) isolates also belonged to these three CCs. A phylogenetic comparison with mecC-MRSA isolates from all over Europe and New-Zealand showed local adaptations, despite the fact that they all belonged to the same CCs. The acquisition of the SCCmec type XI element by a concomitant MSSA could not be observed in the same animal, but such a transfer might be suggested since identical clones were identified, one MSSA and one MRSA, though in different animals. In parallel, we conducted a detailed analysis of the SCCmec type XI element as well as specific virulence factors (a tst variant and the vwbSaPI gene). Results led us to hypothesize that the mecC gene might be acquired through selective pressure of T. erinacei on MSSA, some of which were acquired a long time ago from ruminants and are now colonizing the skin of the hedgehogs.